Relationship between religious belief and happiness in Oman: a statistical analysis. Issue 7 (8th August 2016) - Hossain, Mohammed Zakir; Rizvi, Mohd Ahsan Kabir
ABSTRACT: This paper explores the relationship between religiosity and happiness among the multicultural people in Oman. A sample of 335 respondents from all walks of life in Oman was analysed using the mean happiness value and their religiousness, religion, age, education level and nationality. The findings were verified using regression and correlation analysis. It was observed that regardless of the religious belief, the level of happiness among people increases with the increasing level of religiousness. The findings could be useful not only to the general public, but also to psychologist and mental health professionals. People with depression, suicidal tendencies, low self-esteem and so on may possibly be treated with religious practices and activities. If such techniques show effectiveness, they may help to bring improvements in mental health and well-being treatments. One unique aspect of this study is that the sample consisted of people from various nationalities, religions and cultural backgrounds living in Oman.